St. Paul's Church Service League History, 1924 - Metcalf, Maud; Ikin, Mrs. A.J.; Metcalf, Maud (St. Paul's Episcopal Church (Bakersfield, Calif.))
Handwritten manuscript documenting the early history of the service groups affiliated with St. Paul's Episcopal Church in Bakersfield, and a report of their 1923 events and fundraising efforts.